Programa desarrollo personal basado en el enfoque centrado en soluciones y adaptación de conductas en estudiantes universitarios - Trujillo 2019 - Nomberto Mercado, Fiorella Anais (2023)
The objective of this research work is to determine the influence of the personal development program based on the solution-focused approach in improving behavioral adaptation in incoming students of the Universidad Privada del Norte - Trujillo 2019. The sample size consisted of 45 students, from the psychology degree. This research is of pre-experimental design since it has a pre and post-test. The hypothesis testing data were collected using the Behavior Adaptation Inventory (IAC), which is made up of 123 items, and the statistical processing was performed using the SPSS statistical software. As a result, in the Pre-Test, it was obtained that 55% of the students are located at a medium level and 40% at a low level in their adaptation of behaviors; After the execution of the program, no student showed a low level and 44.4% increased their behavior adaptation to a high level. It is concluded that the Student's T statistical test finds evidence to establish that the increase in the average registered by the students after the application of the Program (91.2) with respect to that obtained before its application (69.8), is highly significant (p< .01).